Is raw better? A multiple DNA barcoding approach (full and mini) based on mitochondrial and nuclear markers reveals low rates of misdescription in sushi products sold on the Italian market. (September 2017) - Armani, A.; Tinacci, L.; Lorenzetti, R.; Benvenuti, A.; Susini, F.; Gasperetti, L.; Ricci, E.; Guarducci, M.; Guidi, A.
Abstract: New dietary habits have favored an ever growing popularity of Eastern country cooking style and in particular of sushi. Even though the Reg. (EU) 1379/2013 does not apply to restaurants and caterers, the Reg. (EU) 1169/2011 establishes that all the information they provided to the final consumer have to meet the transparency requirements as regards the description of the ingredients used for the preparation of food. The present study aimed at performing a molecular based survey to identify the seafood species used in the sushi preparations at the retail level. A total of 185 samples were collected from sushi venues and supermarkets and DNA barcoding, followed by a pairwise divergence and Neighbor Joining clustering analysis, was applied in order to verify the information declared at purchase. Rather than to a proper training of Food Business Operators working at the catering level, the low mislabeling rate found in this study (3.4%) could be ascribed to the standardization of the products sold in ethnic restaurants. In fact, the common practice of proposing standardized menus always relying on the same species of fish could limit the risk of mislabeling occurrence. Highlights: A two years-survey was carried out on sushi products sold in Italy at retail level. 185 sushi samples were collected and subdued to DNA barcoding analysis. A low misdescription rate (3.3%) was found. Results reflect a proper training of FBO towards labelling.